Intracameral antibiotics: Safety, efficacy, and preparation - Braga-Mele, Rosa; Chang, David F; Henderson, Bonnie An; Mamalis, Nick; Talley-Rostov, Audrey; Vasavada, Abhay (Journal of cataract and refractive surgery, 2014)
Endophthalmitis is a rare but potentially devastating complication of cataract surgery. This article presents an overview of endophthalmitis prophylaxis and the use of intracameral antibiotics. It highlights available intracameral antibiotics with respect to pharmacology, spectrum of activity, dosage and preparation, safety, and efficacy profiles, as well as toxic anterior segment syndrome risks to better define the potential use of these medications in the prevention of endophthalmitis. Proprietary or commercial disclosures are listed after the references.